Match-play demands and anthropometric characteristics of national and international women's fifteen-a-side rugby union: a systematic scoping review - Curtis, C.; Mitchell, S.; Russell, M. (The Journal of Strength and Conditioning Research, 2023)
An increased professionalization within women's 15-a-side rugby union (R15s) has prompted greater sports science support and a need to better understand demands of the sport. Online database (PubMed, MEDLINE, and SPORTDiscus) searches were performed according to the PRISMA Scoping Review protocol. Studies were eligible if match-play demands or anthropometric characteristics of women's R15s players were investigated. After calibration exercises, the lead and senior authors independently quality assessed each study. A total of 1,068 studies were identified; 15 of which met the study criteria. The mean total match-play distance covered was 5,378 ± 626 m (forwards: 5,188 ± 667 m and backs: 5,604 ± 609 m), with first half values exceeding second half (2,922 ± 87 m vs. 2,876 ± 115 m). The mean relative distance (RD) (72.0 m·min-1) was greater than their male counterparts (64.2 m·min-1-68.2 m·min-1). Backs were exposed to more severe collisions compared with forwards (6 ± 1 vs. 5 ± 4). Work:rest ratios ranged between 1.0:0.7-1.0:0.9. Regarding anthropometric characteristics, the mean lean and fat mass was reported as 51.9 ± 5.2 kg and 18.6 ± 4.6 kg, respectively. The mean body fat percentage was 24.7 ± 5.4%. The mean bone mineral density and bone mineral content was 1.27 ± 0.04 g·cm-2 and 3.07 ± 0.2 kg, respectively. This scoping review summarizes the current evidence base and key findings relating to the match-play demands and anthropometric characteristics that can be used in practice to inform player welfare and sport science support to women's R15s players at a national and international standard. Numerous gaps in our understanding of how best to develop and optimize performance, physical demands, and anthropometric characteristics of women's R15s players remain.